A French Legacy: The Transition from Collegiate to Bureaucratic Record-Keeping in a Dutch Town, 1800-1900 - Horsman, Peter J. (Archivaria, 2006)
Initiated by political and administrative changes that started in 1795, record-keeping in the Netherlands underwent a metamorphosis. The alterations were greatly influenced by French practices during the period that the country was under French control and administration. However, many of the traditional record-keeping methods were preserved and mixed with the French practices. Local administrations, like those of the town of Dordrecht, seem largely to have escaped from French influence on their record-keeping. However, increasing paperwork enforced bureaucracy, and the bureaucracy imposed its administrative rules on the local political hierarchy, such as the city council and the committee of burgomaster and aldermen. The Dordrecht case study demonstrates how record-keeping moved from the primary process of decision making to become a bureaucratic specialty, which met the requirements of the bureaucracy itself rather than those of the political decision makers. The beginning of the twentieth century witnessed the birth of a formal record-keeping system, controlled by a specialized registry. RÉSUMÉ La gestion de documents aux Pays-Bas se métamorphose à la suite de changements politiques et administratifs qui s’enclenchent en 1795. Les changements proviennent en bonne partie de l’influence des pratiques françaises, durant la période où le pays se trouve sous contrôle français. Toutefois, les pratiques traditionnelles en matière de gestion des documents survivent et se combinent aux pratiques françaises. Les administrations locales, comme celle de la ville de Dordrecht, semblent avoir échappé à l’influence française directe sur leur gestion de documents. Toutefois, l’importance croissante des écritures renforce la bureaucratie, qui impose ses règles aux élites politiques locales, comme le conseil de ville et le comité des bourgmestres et échevins. Le cas de Dordrecht montre comment la gestion de documents s’éloigne des processus de prise de décision pour devenir une spécialité bureaucratique, qui répond aux besoins de la bureaucratie plutôt qu’à ceux des décideurs politiques. Le début du XXe siècle voit l’apparition d’un système formel de gestion de documents, contrôlé par un registre spécialisé.